Community Service for Students’ Development: Strengthening IPAS Digital Teaching Media Competence Through Book Creator at SDIT Darul Istiqomah Palangka Raya - Norhalizah, Norhalizah; Maulida, Tasya; Ajijah, Salsabilla Johan; Syabrina, Muhammad; Sulistyowati, Sulistyowati; Qamariah, Zaitun; Yuliani, Hadma (PT. Amirul Bangun Bangsa, 2025)
The use of technology in learning remains a challenge for many prospective elementary school teachers, particularly in developing interactive and engaging digital teaching media. At SDIT Darul Istiqomah, Palangka Raya City, the limited ability of PGMI students to utilize technology has hindered the effectiveness of IPAS learning. In response, a collaborative Community Service (PKM) initiative involving PGMI lecturers and students was carried out to enhance the competence of future teachers in developing digital teaching materials using the Book Creator platform. This program applied the Asset-Based Community Development (ABCD) approach, emphasizing the empowerment of existing strengths within the community. The implementation involved a series of activities, including training sessions, technical assistance, and classroom-based evaluations of the media developed. Pretests and posttests were administered to assess participants’ improvement, and classroom observations were conducted to evaluate the application of the digital media. The results showed that 90% of participants improved their skills in creating digital teaching materials, and 85% of elementary students reported increased motivation when learning with the interactive media produced. This community service activity not only strengthened the digital media competencies of PGMI students but also contributed to improving the quality of technology-based learning in partner schools. Through collaborative engagement between lecturers, students, and the school community, the program supported the broader agenda of digital transformation in basic education.